Uncertainty analysis of liquid flow rate measurement with the pressure–time method. (November 2021) - Adamkowski, Adam; Janicki, Waldemar; Lewandowski, Mariusz; Costa Bortoni, Edson da
Highlights: The innovative procedure of uncertainty estimation in the pressure–time (PT) method. Analysis of the simplifications of the PT method and their impact on uncertainty. Impact of the determination of losses and irregularities in flow on uncertainty. Two cases of practical use of the proposed uncertainty estimation procedure. Reference of the results to the requirements of the standards for the PT method. Abstract: The paper presents the procedure developed for calculating the uncertainty of the liquid flow rate measurements conducted using the pressure–time method. The procedure is in-line with the recommendations of the current general guidelines concerning measurement uncertainty. Significant simplifications of the pressure–time method and their influence on its accuracy were analyzed. An unique method for estimating the uncertainty associated with the standard simplified calculation of friction losses in the measuring section of the pipeline was developed. The procedure also takes into account other influencing factors, including non-stationary phenomena in the flow causing pressure pulsations and uneven pressure distribution in the pipeline measuring section. Two examples of the pressure–time method applications along with the uncertainty estimation are presented. Results allowed referring to the recommendations of the standards concerning the pressure–time method, and they change the common approach to the issue of estimating the uncertainty for measurements carried out with the considered method.